About the gas hydrate potential of the Antarctic continental margin bottom structures (by geophysical data) - S.P. Levashov; N. A. Yakimchuk; I. N. Korchagin; Ju. M. Pischany; V. G. Bakhmutov; V. D. Solovyov; D. N. Bozhezha (Ukrainian Antarctic Journal, 2014)
Data on the location of BSR-zones and possible accumulations of gas hydrates in the structures of passive continental margins of Antarctica are summarized. The efficiency of the new innovative technology of geoelectric and remote geophysical methods using for the study of gas hydrate accumulations and deep cuts with abnormally polarized layers of the "deposit of gas hydrates" building is given. An important feature of this proposed technology is that it can be used as an independent indicator of gas hydrates detecting in areas with BSR-boundaries of different genesis. New gas hydrate accumulations near the Academician Vernadsky UAS were identified and their position in the sediment section with high accuracy were defined. It’s shown, that the region near the South Shetland Islands can be assigned to one of the most promising areas (with the area in the western part of Ross Sea) accumulations of gas hydrates in Antarctica.